Ayioryitika : the 1928 excavations of Carl Blegen at a Neolithic to Early Helladic settlement in Arcadia - Petrakis, Susan L. (Prehistory monographs, 2002)
Ayioryitika, a large open-air settlement in Arcadia, in central Greece, was inhabited during the Neolithic and Early Bronze Age. It was excavated in 1928 by Carl Blegen under the auspices of the American School of Classical Studies at Athens, but the research was never published. The site is particularly important for its beautifully decorated Middle Neolithic pottery and for its figurines of human figures and animals. This volume gathers together the scattered and fragmentary evidence for the excavation and its finds. For the first time, the information from this large and important early tow.